Communication of the TeleCTG innovation diffusion process with midwives’ participation and empowerment - Retor Aquinaldo Wirabuanaputera Kaligis; Faridhian Anshari; Sofia Primalisanti Devi (Jurnal Kajian Komunikasi, 2021)
TeleCTG is a telemedicine-based medium technology that Indonesia makes. Nowadays, Cardiotocography has only been operated by an obstetrician/gynecologist (ob-gyn) at the hospital. The occurrence of TeleCTG at Puskesmas (the public health center) helps midwives send the diagnosis online to an ob-gyn for immediate response. This technology helps to equalize the quality of health services. The research purpose is to analyze the innovation diffusion process in using TeleCTG medical devices for participation and empowerment of midwives as the frontline of public health services in the Kupang. Diffusion of innovation is a persuasive process of spreading innovation through specific channels among the members of a social system. Using an exploratory sequential mixed-methods design, then this research explored qualitative data through in-depth interviews with four informants. Questionnaires were distributed to draw the generalizability of the findings at the population level. The population is midwives from 13 sub-districts using TeleCTG in Kupang and cluster sampling techniques. Path analysis is used to see the causal relationship among elements of innovation diffusion, midwives’ participation, and midwives’ empowerment. The results found that the diffusion of innovation encourages the participation of midwives, then the participation level increases empowerment. The diffusion of innovation does not directly influence the empowerment of midwives, but there is an indirect effect of the elements on the empowerment mediated by midwives’ participation. As the final discussion, the participation of midwives is the key to increasing the empowerment of Puskesmas midwives in Kupang.